Long-Term Potentiation of Excitatory Synaptic Strength in Spinothalamic Tract Neurons of the Rat Spinal Cord - Hur, Sung Won (The Korean Physiological Society and The Korean Society of Pharmacology, 2013)
Spinal dorsal horn nociceptive neurons have been shown to undergo long-term synaptic plasticity, including long-term potentiation (LTP) and long-term depression (LTD). Here, we focused on the spinothalamic tract (STT) neurons that are the main nociceptive neurons projecting from the spinal cord to the thalamus. Optical technique using fluorescent dye has made it possible to identify the STT neurons in the spinal cord. Evoked fast mono-synaptic, excitatory postsynaptic currents (eEPSCs) were measured in the STT neurons. Time-based tetanic stimulation (TBS) was employed to induce long-term potentiation (LTP) in the STT neurons. Coincident stimulation of both pre- and postsynaptic neurons using TBS showed immediate and persistent increase in AMPA receptor-mediated EPSCs. LTP can also be induced by postsynaptic spiking together with pharmacological stimulation using chemical NMDA. TBS-induced LTP observed in STT neurons was blocked by internal BAPTA, or Ni(2+), a T-type VOCC blocker. However, LTP was intact in the presence of L-type VOCC blocker. These results suggest that long-term plastic change of STT neurons requires NMDA receptor activation and postsynaptic calcium but is differentially sensitive to T-type VOCCs.